PENGARUH MODEL PEMBELAJARAN SAINS TERINTEGRASI MATEMATIKA BERBASIS MASALAH TERHADAP SIKAP ILMIAH - Siti Suhailah Rangkuti; Yanti Fitria; Yeni Karneli (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
The purpose of this research was to determine the scientific attitude of students by applying a problem-based mathematics integrated science learning model. This type of research is a quantitative research with a quasi-experimental method. The study population was all students of grade V SDN 0102 Sibuhuan. The sample of this research is class V A and V B. The data collection method used was to distribute scientific attitude questionnaires to all students. The results showed that the scientific attitude of students who applied the problem-based integrated mathematics learning model was better than conventional learning.